A high performance all-solid-state flexible supercapacitor based on carbon nanotube fiber/carbon nanotubes/polyaniline with a double core-sheathed structure. (1st September 2018) - Liu, Jia-hua; Xu, Xiao-ying; Lu, Weibang; Xiong, Xinbo; Ouyang, Xing; Zhao, Changhui; Wang, Fei; Qin, Si-yin; Hong, Jiao-ling; Tang, Jiao-ning; Chen, Da-Zhu
Abstract: A new type of ternary carbon nanotube fiber (CNF)/three-dimensional (3D) porous carbon nanotubes (CNTs)/polyaniline (PANI) electrodes with a double core-sheathed architecture composed of CNF/CNTs and CNTs/PANI was fabricated via low-potential electrophoretic deposition of CNTs and subsequent electrochemical polymerization of PANI on the CNF surface. The resulting all-solid-state supercapacitor possesses a high specific capacitance of 67.31 mF cm −2 at the current density of 0.5 mA cm −2 and only a loss as less as 10% of its initial specific capacitance after 5000 charge-discharge cycles. Furthermore, it is capable of withstanding different bending deformations, and can maintain 99.8% capacitance, even after experiencing the bending of 180° for 500 times, which manifests a significant application potential in the field of flexible electronic devices. Graphical abstract: Image 1 Highlights: The fiber electrodes modified with 3D porous CNTs and polyaniline were realized. The decorated ternary fiber based all-solid-state supercapacitor was fabricated. The capacitance of the supercapacitor was remarkably enhanced. The supercapacitor demonstrated an excellent cyclic stability. The supercapacitor kept a high level of capacitance after bending 500 times.